Curcumin in Sepsis: Anti-Inflammatory Mechanisms, Nano-Formulations, and Evidence from Preclinical and Early Clinical Studies - Yeni Puspawani; Gusbakti Rusip; Ali Napiah (CoinReads Media Prima, 2026)
Introduction: Sepsis is driven by dysregulated host inflammation, cytokine amplification, endothelial injury, and oxidative stress, with nuclear factor kappa B signaling acting as a central regulatory axis. Curcumin, the principal bioactive compound of turmeric, has gained attention as a potential adjunctive therapy because of its pleiotropic anti-inflammatory, antioxidant, and immunomodulatory properties; however, its translational relevance in sepsis remains unclear. Methods: This narrative review synthesizes evidence from preclinical sepsis models, mechanistic studies, systematic reviews, meta-analyses, and early randomized or controlled clinical trials that evaluated curcumin, nano-curcumin, or curcumin-based formulations for sepsis and critical illness. Results: Preclinical evidence indicates that curcumin attenuates macrophage hyperactivation, suppresses TNF-α, IL-6, and IL-1β signaling, and modulates pyroptosis-related inflammatory pathways. In polymicrobial sepsis models, curcumin inhibited the HMGB1/TLR4/NF-κB pathway, reduced HMGB1 release, and limited NF-κB p65 nuclear translocation in polymicrobial sepsis models. Higher doses demonstrated stronger protection against multi-organ injury, partly through ferroptosis suppression via ACSL4/glutathione peroxidase 4 (GPX4) regulation and inhibition of protein lactylation via p300 downregulation. Early ICU trials suggest that enterally administered nano-curcumin may reduce inflammatory and endothelial biomarkers while enhancing antioxidant responses via Nrf2 signaling. Clinical signals include improved SOFA scores and reduced mechanical ventilation duration, although mortality and ICU length-of-stay remain inconsistent. Pooled evidence from critically ill populations also indicates modest improvements in organ dysfunction and selected hepatic and nutritional biomarkers. Conclusion: Curcumin demonstrates strong biological and translational plausibility in sepsis through multi-target modulation of inflammatory, oxidative, and cell death pathways. However, current clinical evidence remains limited and heterogeneous, underscoring the need for larger, well-designed trials with standardized formulations and clinically meaningful endpoints.